Islam's View of Pluralisme:A Study of Maudhu'i Tafsir - Lalu Bustanil ulum; Novi Amelia Putri; Nur Farhati (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2024)
This research discusses the Islamic perspective on diversity and efforts to create harmony between religious differences. The primary sources of this research are the Koran, hadith, and the words of scholars about diversity. Meanwhile, the secondary sources of this research are derived from the literacy of several articles. The results of this study highlight the importance of communication and mutual understanding in creating a friendly environment for all. This research will also deepen our understanding of Islamic diversity and encourage peace-building between people of different faiths. Then, this research is conducted using the thematic approach method, which is to collect verses related to pluralism and identify the interpretation of the verse by clarifying the background of the revelation of verses related to pluralism and its relationship with other verses in the Qur'an.